Epidemiology and risk factors of self-reported systemic allergic reactions to a Hymenoptera venom in beekeepers worldwide: a protocol for a systematic review of observational studies - Igor Locatelli; Tanja Carli; Mitja Košnik; Andreja Kukec (BMJ Open)
Introduction Systemic allergic reaction (SAR) to a Hymenoptera venom is a potentially life-threatening disorder. The rate of SAR between beekeepers in comparison with a healthy individual is different. The risk for an SAR is particularly high in beekeepers due to their persistent or seasonal exposure to the stinging Hymenoptera. We aim to provide a critical appraisal and a synthesis of evidence-based data from epidemiological observational studies, focusing on SARs to a Hymenoptera venom and the associated risk factors for SARs in beekeepers worldwide.Methods and analysis Searching will include seven electronic databases for published studies without language restrictions, from inception up to 3 August 2021, and it will be rerun for all electronic databases prior publication. Only epidemiological observational studies in beekeepers will be included. The risk of bias in the included studies will be appraised by using the Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross-Sectional Studies and the Newcastle-Ottawa Scale, adapted for cross-sectional studies. For the certainty of evidence, the Grading of Recommendations Assessment, Development and Evaluation approach will be used. Qualitative synthesis will be presented in a tabulated format with the selected characteristics across primary studies and the main outcome of interest. A meta-analysis is planned to be performed if there will be a sufficient number of homogeneous studies with complete data. The Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2015 statement will guide the reporting of this systematic literature review.Ethics and dissemination No ethics approval is needed to conduct the systematic literature review since it will be solely based on the published literature. Findings will be disseminated through the relevant conferences, peer-review and open-access journals.PROSPERO registration numberCRD42021260922.